Sharing Jesus with Hindus : global witness among Hindu diaspora - George, Sam; Kumar, Ashok (Pasadena, CA. William Carey Publishing., 2024)
"Building Authentic Relationships with Hindus Indians make up the world's largest diaspora community, and most of them are Hindus of diverse backgrounds, languages, and cultures. Millions of Hindus have migrated abroad in recent decades and are well-settled in different countries while many more are expected to be dispersed far and wide in the coming years. Many of them are highly educated and skilled, professionally successful, culturally adaptive, and very religious in their outlook. Sharing Jesus with Hindus is the collective wisdom of many seasoned ministry leaders and practitioners about how to minister effectively to contemporary global Hindus. The contributors are situated in different parts of the world, and some come from Hindu backgrounds themselves. Emerging from an international conference on mission to and among Hindus worldwide, this book provides practical ministry strategies and scholarly reflections drawn from decades of insight. The authors have experience in diasporic living and ministering to Hindus in diverse contexts. Learn how to share the gospel of Jesus Christ with your new neighbors from the Indian subcontinent. Avoid common mistakes and be an effective Christian witness to Hindus globally. Here is an essential resource in the toolkit of every church and Christian ministry worldwide"--
Includes bibliographical references (pages 209-223).
Keywords: Missions to Hindus; Hindu diaspora